ZBTB20 in Nociceptive Neurons of the Trigeminal Ganglia Regulates Pruritus - Jia, Xin; Dai, Meng-Han; Ren, An-Jing; Wang, Ting-Ting; Zhang, Weiping J.; Zhang, Ling (Frontiers in Medicine, 2021)
Recent studies have shown that ZBTB20, a zinc-finger protein containing transcription factor, is highly expressed in small-diameter primary sensory neurons in mice, and modulates pain through regulating TRP channels. However, whether ZBTB20 regulates itch sensation has not been demonstrated. In this study, small-diameter primary sensory neuron-specific ZBTB20 knockout (PN-ZB20KO) mice were used to investigate the role of ZBTB20 in the regulation of itch sensation. First, both histamine-dependent and nonhistamine-dependent itch behaviors induced by injection of histamine and chloroquine (CQ) into the cheek were significantly diminished in PN-ZB20KO mice. Second, double immunohistochemistry showed that ZBTB20 was mainly expressed in CGRP-labeled small peptidergic neurons and was expressed at low levels in IB4-labeled small nonpeptidergic and NF200-labeled large neurons in the trigeminal ganglia (TG). ZBTB20 was also expressed in most TRPV1+ and TRPA1+ neurons and to a lesser extent in TRPM8+ neurons in the TG. Furthermore, cheek injection of histamine and CQ enhanced the mRNA expression of TRPV1 and TRPA1 but not TRPM8 in the TG. Moreover, TRPV1 and TRPA1 knockout (KO) mice exhibited attenuation of itch behavior induced by histamine and CQ, respectively. Finally, silencing endogenous ZBTB20 with recombinant lentivirus expressing a short hairpin RNA against ZBTB20 (LV-shZBTB20) in TG neurons attenuated histamine- and nonhistamine-induced itch and downregulated TRP channels in the TG. Our study suggests that ZBTB20 plays an important role in mediating itch in small primary sensory neurons.